Review of Onyx Cobb (Nematoda: Desmodoridae) with description of two new species from the Yellow Sea, China - Huang, Y.; Wang, H. (Journal of the Marine Biological Association of the United Kingdom, 2015)
Genus Onyx Cobb, 1891 has been reviewed and 19 valid species including two new species have been reported in the world. Two new species, Onyx rizhaoensis sp. nov. and Onyx minor sp. nov. from the Yellow Sea coast are described and illustrated. In addition to the genus characters Onyx rizhaoensis sp. nov. has relatively long cephalic setae; a single loop-shaped amphidial fovea; 12 S-shaped tubular precloacal supplements in 10 + 2 arrangement, posterior 10 closely spaced, anterior two set apart; female vulva situated at almost midpoint of the body. Onyx minor sp. nov. is characterized by a relatively small body for the genus (body length usually shorter than 800 mm); gubernaculum slender parallel to spicules and with a hooked dorsal apophysis; 12 S-shaped tubular precloacal supplements fairly evenly spaced; female vulva situated at about midbody. At the same time, a dichotomous key for Onyx males is proposed.